OPTIMALlSASI PRODUKSI TEBU DENGAN PROGRAM LINEAR PADA PABRIK GULA TAKALAR SULAWESI SELATAN - Amran Sulaiman (Jurnal Keteknikan Pertanian, 2007)
ABSTRACTThe aim of the optimization of sugar cane production at PG Takalar is allocate all resources proportionally to get the maximal production according to factory design attached witt relatively low cost. The optimizetion was conducted with linear programming. The result showed that optimal planting period for the plant cane is June, July. October, and November, while for retoon is June up to November. The varieties those give the optimal production is Camp, F.154, Others, PS.61, PS.85-1. Q.81, and ROC. 10. The optimal portion of plant category was 25% plant cane, 30% retoon I. 25% retoon II and 20% of ratoon III. By optimization, the total area of 3.213 ha potentially can produce 192.036. 13 ton/year, which is increase about 115% from the regular practice. Keyword: Linear programming, optimization, plant cane, sugar cane Diterima: 30 Oktober 2007: Disetujui:22 Nopember 2007